PENGARUH KETERAMPILAN SISWA DAN PRAKTEK LAPANGAN TERHADAP MOTIVASI BERWIRAUSAHA SISWA SMKN 1 SOLOK JURUSAN BISNIS DARING DAN PEMASARAN - Nesi Safria; Rasidah Nasrah (Jurnal Bina Bangsa Ekonomika, 2022)
This research was conducted at SMKN 1 Solok. The purpose of this study was to determine how much influence Student Skills and Field Practice had on Entrepreneurial Motivation of Students at SMKN 1 Solok, Department of Online Business and Marketing. The population in this study amounted to 84 people. Types of quantitative research. The sampling technique used purposive sampling method and in this study the sample was class XII BDP 3, which consisted of 30 people. The data collection technique used is by using a questionnaire or questionnaire. Based on multiple linear regression analysis of Student Skills and Field Practice variables affect the Entrepreneurial Motivation of Students at SMKN 1 Solok Y = 2.408 + 0.744X1 + 0.293X2 + e. From the t-test conducted, it was found that the variable X1 Student Skills had a significant effect on Student Entrepreneurial Motivation with tcount greater than t table 7.735> 2.05 and a significant level value of 0.000 <0.05 then H0 was rejected and Ha was accepted. Variable X2 Field Practice has a significant effect on Student Entrepreneurial Motivation, the known value of t count > t table is 3.008 > 2.05 and the significance value is 0.006 < 0.05, then H0 is rejected and Ha is accepted. From the f test conducted, it was found that students and field practice had a simultaneous effect on students' entrepreneurial motivation with f fcount 44,038 > ftable 3,354 with a significance value of 0.000 < 0.05, then H0 was rejected and Ha was accepted. From the Determination Test, the value of R square is 0.765 or 76.5%. This indicates that the contribution of the variable Student Skills and Field Practice is 76.5%. While the remaining 23.5% is influenced by other variables